2016
DOI: 10.1016/j.psyneuen.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Early adversity, hypocortisolism, and behavior problems at school entry: A study of internationally adopted children

Abstract: The hypothalamic-pituitary-adrenal (HPA) axis is influenced by early life adversity; however, less is known about the potential for recovery following marked improvements in care. The present study examined longitudinal changes in children’s cortisol reactivity in the laboratory (4 assessments over 2 years) after adoption. Post-institutionalized (N=65) and post-foster care children (N=49) demonstrated blunted reactivity relative to non-adopted peers (N=53). Furthermore, post-institutionalized children exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
123
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 32 publications
12
123
2
Order By: Relevance
“…Group differences in the CAR with a complete lack of a response in the most severely deprived and an attenuated pattern in the group with short duration of deprivation are consistent with the fairly uniform observation of a pattern of hypocortisolism in institutionalized and postinstitutionalized children at much younger ages. Our findings are also consistent with a previous finding that late removal from institutions (between 18 and 24 months) is associated with hyporeactivity in response to stress, while the same is less apparent with earlier removal (Koss et al, 2016;McLaughlin et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Group differences in the CAR with a complete lack of a response in the most severely deprived and an attenuated pattern in the group with short duration of deprivation are consistent with the fairly uniform observation of a pattern of hypocortisolism in institutionalized and postinstitutionalized children at much younger ages. Our findings are also consistent with a previous finding that late removal from institutions (between 18 and 24 months) is associated with hyporeactivity in response to stress, while the same is less apparent with earlier removal (Koss et al, 2016;McLaughlin et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…It cannot be ruled out that disturbed cortisol regulation is a late appearing consequence of institutional deprivation. However, given findings by other groups who have prospectively assessed HPA axis function in institutionalized and post-institutionalized children (Koss et al, 2016;McLaughlin et al, 2015), and given our own findings of early appearing deprivationspecific problems which are highly persistent and are not eradicated by the overall very positive post-adoption experience, it is likely that HPA axis dysregulation also constitutes an early appearing and stable phenotype associated with institutional rearing. In light of the evidence of decreased cortisol activity and reactivity in adults and children with experience of early adversity (Carpenter et al, 2007;Elzinga et al, 2008;Lovallo et al, 2011;Miller et al, 2007;Power et al, 2012;Schwaiger et al, 2016), it has been proposed that sustained periods of chronic stress, such as psychosocial deprivation and neglect, are initially associated with high levels of circulating cortisol, followed by counter-regulation which eventually results in decreased HPA axis re-/ activity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, Koss et al (2016) found that blunted diurnal decline was associated with a blunted cortisol response toward a laboratory challenge in a group of predominantly adopted children. Differences between the study populations may at least in part underlie the differences in results.…”
Section: Discussionmentioning
confidence: 95%
“…Research in 1.5-to 5-year-old (predominantly adopted) children showed that both lower morning cortisol concentrations and blunted diurnal change were associated with blunted cortisol stress responses (Koss et al, 2016). However, research on the dynamics of HPA-axis functioning in normally developing children at the beginning of elementary school is still scarce.…”
mentioning
confidence: 99%